2008
DOI: 10.1136/adc.2006.113506
|View full text |Cite
|
Sign up to set email alerts
|

Once-daily amoxicillin versus twice-daily penicillin V in group A  -haemolytic streptococcal pharyngitis

Abstract: In this adequately powered study, once-daily oral amoxicillin is not inferior to twice-daily penicillin V for the treatment and eradication of GABHS in children with pharyngitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(43 citation statements)
references
References 43 publications
1
39
0
3
Order By: Relevance
“…По данным мета-анализа, распространенность БГСА-инфекции у детей до 18 лет с острым фарингитом составляет 37% [95% доверительный интервал (confidence interval, CI) [32][33][34][35][36][37][38][39][40][41][42][43]. В младшей возрастной группе частота стрептококкового фарингита меньше и не превышает 24% (95% CI [21][22][23][24][25][26].…”
Section: Introductionunclassified
“…По данным мета-анализа, распространенность БГСА-инфекции у детей до 18 лет с острым фарингитом составляет 37% [95% доверительный интервал (confidence interval, CI) [32][33][34][35][36][37][38][39][40][41][42][43]. В младшей возрастной группе частота стрептококкового фарингита меньше и не превышает 24% (95% CI [21][22][23][24][25][26].…”
Section: Introductionunclassified
“…Several recent randomised comparative trials demonstrated noninferiority of once-daily amoxicillin versus twice-daily amoxicillin or penicillin V. 11,12 In this regard, an orally administered antibiotic for the treatment of GABHS pharyngitis that could be given once daily would be convenient, particularly for children attending school and may also result in improved compliance.…”
Section: Amoxycillinmentioning
confidence: 99%
“…Currently, the AHA-AAP, IDSA and Spanish guidelines recommend amoxicillin once or twice daily for 10 days as alternative first-line therapy [16,27,28]. In comparative clinical trials, once-daily amoxicillin (50 mg/kg, to a maximum of 1000 mg) for 10 days has been shown to be effective for GAS pharyngitis [57,58]. It has the advantage of once-daily dosing, which may enhance compliance.…”
Section: Treatment Optionsmentioning
confidence: 99%